Communism : from Marx's Manifesto to 20th-century reality - Forman, James D. (New York : Watts, 1979)
Surveys the history of communism, examines the emergence and implications of Eurocommunism, and considers the impact of communism on Third World politics.
Includes index.
Bibliography: p. 141-145.
Keywords: Communism -- History -- Juvenile literature; Communism -- History